A review of financing and human capital development issues among micro enterprises in Afghanistan - Haqbin, Naqibullah; Mohd Thas Thaker, Mohamed Asmy; Abd Jalil, Mohamad Isa; Hamzah, Ahmad Aizudin (Universiti Malaysia Sabah, 2023)
This paper's primary objective is to investigate the obstacles related to financing and human capital development that hinder the growth of micro enterprises (MEs) and their contribution to the overall economic progress of Afghanistan. Evidently, MEs in this country are grappling with significant financing challenges, including high financing costs, stringent collateral requirements, rigorous documentation criteria, the need for comprehensive business plans, and the necessity for robust financial records. Moreover, MEs are also confronting issues related to human capital development, such as a lack of administrative and managerial skills, inadequacies in training courses and programs, low levels of education, limited entrepreneurship knowledge, and financial literacy. Despite the Afghan government's efforts to address these financial and human capital development issues, they continue to impede the growth of MEs. Consequently, this study seeks to conduct a comprehensive examination of these challenges through content analysis. By shedding light on these problems, this research aims to offer clear insights and recommendations for addressing the issues related to financing and human capital development in Afghanistan.